2018
DOI: 10.3389/fmicb.2018.03068
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Distribution and Genetic Diversity of Rice Stripe Mosaic Virus in Southern China

Abstract: Rice stripe mosaic virus (RSMV) transmitted by the leafhopper Recilia dorsalis is a tentative new species in the genus Cytorhabdovirus identified recently in South China. To explore its geographic distribution and genetic diversity, field investigation and viral whole-genome sequencing were conducted in this study. The results indicated that RSMV was present in the rice samples collected across southern China. Twelve representative samples from different geographical regions were selected for viral whole-genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…A phylogenetic tree showed that the GGVA populations could be divided into two groups. However, in contrast to most geminiviruses or some RNA viruses ( Rocha et al, 2013 ; Yang et al, 2018 ), this observation revealed some GGVA isolates from the same geographical region were located in different clades. This might be explained by the fact that the vegetative propagation of grapevine favors viral accumulation in the propagation material, and subsequently this virus is disseminated globally with the grapevine material.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…A phylogenetic tree showed that the GGVA populations could be divided into two groups. However, in contrast to most geminiviruses or some RNA viruses ( Rocha et al, 2013 ; Yang et al, 2018 ), this observation revealed some GGVA isolates from the same geographical region were located in different clades. This might be explained by the fact that the vegetative propagation of grapevine favors viral accumulation in the propagation material, and subsequently this virus is disseminated globally with the grapevine material.…”
Section: Discussionmentioning
confidence: 78%
“…The C2 protein of tomato leaf curl Taiwan virus was shown to be an important pathogenicity determinant, which interferes with host DNA methylation ( Tu et al, 2017 ). To counteract RNA silencing defenses in plant, many geminivirus V2 proteins have been shown to serve as RNA silencing suppressors ( Yang et al, 2018 ). Glick et al (2008) confirmed that the interaction between suppressor of gene silencing 3 (SGS3) and V2 was required for the suppressor activity of V2 encoded by TYLCV.…”
Section: Discussionmentioning
confidence: 99%
“…From 2015 to 2016, RSMD only occurred in southwestern Guangdong in southern China; Luoding rice areas had the most serious occurrence, with a 70% field incidence. From 2016 to 2018, the disease gradually spread throughout southern China, and diseased plants were found in eight rice-growing areas in Guangdong province (Yunfu, Maoming, Zhanjiang, Yangjiang, Huizhou, Heyuan, Shaoguan, and Meizhou), four rice-growing areas in Guangxi province (Wuzhou, Hezhou, Yulin, and Qinzhou), and two rice-growing areas Hainan province (Ding’an and Tunchang County; Yang et al, 2018 ). Among them, Yunfu city in Guangdong province was the most affected, with 165 fields under investigation.…”
Section: Geographical Distributionmentioning
confidence: 99%
“…Currently, 13 RSMV isolates from the Guangdong, Guangxi, and Hainan provinces can be found in the GenBank database. Sequence analysis showed that the nucleotide and amino acid sequences of 13 RSMV isolates were highly conserved and shared 99.4–100% and 98.9–100% identity, respectively ( Yang et al, 2018 ). RSMV isolates from all over Guangdong share a lower nucleotide identity between them than isolates from Guangxi and Hainan, suggesting that the virus may have originated in Guangdong ( Yang et al, 2018 ).…”
Section: Viral Genomic Structure and Genetic Variationmentioning
confidence: 99%
“…Recent emerging plant rhabdoviruses transmitted by insect vectors in a persistent-propagative manner cause substantial agricultural losses (Fang et al, 2019;Di et al, 2014;Liu et al, 2018;Yang et al, 2017Yang et al, , 2018. Rice yellow stunt virus (RYSV), an insect-transmitted rice nucleorhabdovirus, was first identified in 1965 in Taiwan and Guangdong provinces of China (Chiu et al, 1965;Fan et al, 1965).…”
Section: Introductionmentioning
confidence: 99%